Chaucer and the cultures of love and marriage - Hume, Cathy (Bristol studies in medieval cultures., 2012)
Chaucer's preoccupation with love and marriage has been a focus of criticism for more than a century. Here, the love relationships and marriages in six of the 'Canterbury Tales, Troilus and Criseyde', and the 'Legend of Good Women' are reappraised from a fresh direction, using late medieval letter collections and advice literature for women to shed new light on the competing cultures of love and marriage that troubled both Chaucer himself and his contemporaries. Beginning with a concise summary of the history of marriage in fourteenth-century England, and making use of recent research in social history, the volume goes on to analyse letter collections and advice books in order to reconstruct late medieval ideology and practice. Among other elements, the author discusses the flirtatiousness of court culture, the anti-love discourse of advice literature, courtship conventions, rival models of marriage among the bourgeoisie and aristocracy, and the pathos of arranged marriages.